N‐glycosylation affects the proper folding, enzymatic characteristics and production of a fungal β‐glucosidase. Issue 12 (1st August 2013) - Wei, Wei; Chen, Ling; Zou, Gen; Wang, Qianfu; Yan, Xing; Zhang, Jun; Wang, Chengshu; Zhou, Zhihua
ABSTRACT Heterologous expression of β‐glucosidase is one of the approaches to enhance the efficiency of fungal cellulase preparations. It has been reported that N‐glycosylation affects the structure framework, function and stability of proteins. In this study, a β‐glucosidase from Aspergillus terreus (GenBank: XP_001216552, BglS) was heterologously expressed in Pichia pastoris and Trichoderma reesei. The four asparagine residues were all linked with high‐mannose‐type oligosaccharides in P. pastoris, whereas only N224 carried high‐mannose‐type glycan in T. reesei (the other three sites carried one N‐acetylglucosamine). The long N‐glycan chains on PpBglS weakened its substrate affinity, activity and thermostability. The moderate post‐translational and post‐secretory glycan modification in T. reesei makes it a suitable expression system for BglS. The N224 glycan played a critical role in BglS folding. The elucidation of the correlation between the different N‐glycosylation patterns of BglS and their corresponding enzymatic characteristics is an important step towards improving the activity, thermostability and even production of heterologous β‐glucosidase by glycan engineering. Biotechnol. Bioeng. 2013;110: 3075–3084. © 2013 Wiley Periodicals, Inc.